Cointegrating Relationship between Remittances and Economic Growth in Zimbabwe - Murindagomo, Tinashe Melusi; Chiwira, Oscar (International Journal of Economics and Financial Issues, 2025)
This study examines the short-run and long-run relationships between remittances and economic growth in Zimbabwe from 1980 to 2022, using the Autoregressive Distributed Lag (ARDL) Bounds testing approach. The results reveal that in the long run, remittances significantly boost economic growth, supporting the remittance-development optimism theory. However, in the short run, remittances are statistically insignificant, contradicting some prior studies. Net Official Development Assistance negatively impacts economic growth in both the long and short run, highlighting issues like political misuse and economic distortions. Gross Fixed Capital Formation positively impacts economic growth in the long run but has a negative short-run effect. Additionally, domestic credit to the private sector shows a significant negative short-run impact on economic growth. These findings emphasize the importance of remittances for Zimbabwe's long-term economic growth and highlight the need for policy reforms to enhance the positive impacts of official development assistance and domestic credit. Improving transparency and accountability in official development assistance use, aligning aid with national priorities, and addressing structural issues have potential of fostering sustainable economic growth.